Peluang dan Tantangan Pendidikan Islam di Tengah Arus Global - Sirojul Huda; Nur Cholid; M. Ahsanul Husna (Ikatan Dai Indonesia, 2026)
The wave of globalization brings multidimensional disruptions that redefine the global educational landscape, and Islamic education is no exception. This study aims to comprehensively analyze the opportunities and challenges of Islamic education amid globalization, as well as formulate its theoretical and practical implications for educational institutions. The research method employed is qualitative descriptive-analytical with a library research approach. Data were gathered through a literature review of reputable academic sources, which were subsequently analyzed using content analysis and critical discourse analysis techniques. The results indicate that globalization offers significant opportunities, including theological digitalization, the cosmopolitanism of Islamic values, and the integration of science and religion (such as eco-theology). Conversely, Islamic education faces serious challenges, namely covert epistemological secularization, digital moral decadence (cyber-decadence), and the pragmatic commodification of education. This study concludes that the repositioning of Islamic education requires an integrative-inclusive curriculum reconstruction and the internalization of a positive culture based on local-universal values. Consequently, policymakers and practitioners are urged to transform learning systems to be adaptive to technology without losing their prophetic traditions.